1999
DOI: 10.1111/j.1440-1681.1999.03056.x
|View full text |Cite
|
Sign up to set email alerts
|

THE 5‐HT2 RECEPTOR ANTAGONIST SARPOGRELATE REDUCES URINARY AND PLASMA LEVELS OF THROMBOXANE A2 AND URINARY ALBUMIN EXCRETION IN NON‐INSULIN‐DEPENDENT DIABETES MELLITUS PATIENTS

Abstract: 1. Therapeutic effects of a 5-HT2 receptor antagonist sarpogrelate on microalbuminuria and thromboxane (TX)A2 biosynthesis were examined in non-insulin-dependent diabetes mellitus (NIDDM) patients. 2. In protocol I, the ankle-brachial pressure index (API; an indicator of peripheral blood flow) and urinary albumin excretion (UalbV; an indicator of renal function) were determined in 42 NIDDM patients who had been treated with 300 mg/day sarpogrelate for 8 weeks. In an analysis of the results, the NIDDM patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Also, the enterochromaffin cell 5‐HT content is altered in diabetes, some studies found an increased level of serotonin in small intestine of STZ‐diabetic rats (Martin et al ., 1995; Takahara et al ., 2001), but other showed decreased (Cicin‐Sain & Jernej, 1996) or normal levels of serotonin (Richter et al ., 1986) in the small intestine of alloxan‐ and STZ‐induced diabetic rats. Recently, a clinical study carried out in noninsulin‐dependent diabetes mellitus patients has suggested the potential benefits of the 5‐HT 2 receptor antagonist sarpogrelate in the treatment of diabetic nephropathy (Ogawa et al ., 1999; Doggrell, 2004). In addition, Sandrini et al .…”
Section: Introductionmentioning
confidence: 99%
“…Also, the enterochromaffin cell 5‐HT content is altered in diabetes, some studies found an increased level of serotonin in small intestine of STZ‐diabetic rats (Martin et al ., 1995; Takahara et al ., 2001), but other showed decreased (Cicin‐Sain & Jernej, 1996) or normal levels of serotonin (Richter et al ., 1986) in the small intestine of alloxan‐ and STZ‐induced diabetic rats. Recently, a clinical study carried out in noninsulin‐dependent diabetes mellitus patients has suggested the potential benefits of the 5‐HT 2 receptor antagonist sarpogrelate in the treatment of diabetic nephropathy (Ogawa et al ., 1999; Doggrell, 2004). In addition, Sandrini et al .…”
Section: Introductionmentioning
confidence: 99%
“…Sarpogrelate inhibits vascular smooth muscle cell migration (Tamura et al 1997) and proliferation (Sharma et al 1999) and prevents serotonin-induced coronary spasm in animals (Miyata et al 2000). Because of its antiplatelet effects, sarpogrelate is being used in patients for the treatment of peripheral vascular occlusive disease (Takada et al 1997;Ogawa et al 1999). Furthermore, this drug reduces plasma serotonin concentration in patients with thromboangitis obliterans (Buerger's disease) (Rydzewski et al 1996) and improves the exercise capacity of patients with effort angina, by augmenting collateral circulation (Tanaka et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…A pilot study demonstrated that sarpogrelate improved the symptoms and signs of diabetic nephropathy and neuropathy in three of eight patients with Type 2 diabetes and mild nephropathy [25]. Sarpogrelate also reduced the urinary and plasma levels of thromboxane A 2 and this may be associated with the reduced albumin excretion [26]. Another study demonstrated that sarpogrelate reduced albuminuria in diabetic patients with early-stage diabetic nephropathy within 3 months [27].…”
Section: Introductionmentioning
confidence: 99%